When the Supervisor Needs a Supervisor: A Case-based Guide for Developing Psychotherapy Supervisors. Issue 1 (5th January 2023) - Murray, Aimee; Frank, Amber; Sudak, Donna; Topor, David R.; Ruble, Anne E.
Abstract : Supervision of psychotherapy is recognized as fundamental for attaining competency in psychotherapy. However, there is a lack of training in "best practices" of supervisory skills, and some supervisors may lack contemporary knowledge to support supervisees adequately. Training program leadership challenged by limited time and resources to provide supervisors with the necessary education and support can benefit from additional resources for developing psychotherapy supervisors. The authors present 3 core elements of navigating supervisory challenges: training, open dialogue in supervision, and a formal program-level process. Common issues in psychotherapy supervision are then presented in a case-based format. Reflection questions are included to provide an opportunity to consider a personal approach to the case, while specific guidance based on the literature addresses critical aspects of the case examples. Complex supervisory conflicts can challenge programs, but they are normative to the learning process and promote growth in our supervisors.